American dictators : Frank Hague, Nucky Johnson, and the perfection of the urban political machine - Hart, Steven, 1958- (Rivergate regionals., 2013)
American Dictators is the dual biography of two of America's greatest political bosses: Frank Hague and Enoch "Nucky" Johnson. Packed with compelling information and written in an informal, sometimes humorous style, the book shows Hague and Johnson at the peak of their power and the strength of their political machines during the years of Prohibition and the Great Depression. Steven Hart compares how both men used their influence to benefit and punish the local citizenry, amass huge personal fortunes, and sometimes collaborate to trounce their enemies. Both Hague and Johnson shrewdly integrated otherwise disenfranchised groups into their machines and gave them a stake in political power. Yet each failed to adapt to changing demographics and circumstances. In American Dictators, Hart paints a balanced portrait of their accomplishments and their failures. -- Publisher website